Synthesis and characterization of poly(methylmethacrylate) /SiO2 hybrid membrane - Zulfikar, M. A.; Mohammad, A. W. (2004)
Hybrid organic-inorganic membranes were fabricated using sol-gel technique using poly (methyl methacrylate) (PMMA) and tetraethyl orthosilicate (TEOS) with 80/20 (w/w) ratios with THF solvent. The thin films were then characterized using FTIR, SEM, EDX, DSC, TGA, water permeability and also its molecular weight cut-off. From the preliminary characterization, the hybrid membrane was found to have nano and ultra scale tight pore ranges. FT-IR spectroscopy uncovered all the signature peaks characteristic of silicate structures in the near-surface regions. Fingerprints of Si–O–Si groups in cyclic and linear molecular substructures are present. The SEM image clearly shows that hybrid membranes have homogenous and smooth surface. EDX analysis shows the composition of particles in the membrane. DSC analysis of the membrane show-interesting phenomenon regarding glass transition temperature (Tg). The hybrid membrane was found to have higher Tg than pure PMMA. From TGA analysis, the hybrid membranes were observed to have higher thermal stability than pure PMMA.